(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The comparative analysis of higher education management in different countries has become extremely relevant and highly valuable in the world today. These studies address two important issues: i.e. the exchange of cognitive and advanced experience and definite contribution to the development of Comparative Pedagogy. Furthermore, the article compares the higher education management of the two EAEU member states: i.e. Armenia and Кazakhstan as well as presents similarities and differences, achievements and problems of the management system. In particular, reforms that are implemented both in Armenia and Кazakhstan in the context of the Bologna Process are presented in the article. The present article conducts a comparative analysis of Three Degree Education System, Management System and Assessment System.